Plot size for modelling the spatial structure of sudanian woodland trees. Annals of Forest Science - FONTON, HOUÉDOUGBÉ NOËL; ATINDOGBE, GILBERT; HOUNKONNOU, MAHOUTON NORBERT (My University, 2011)
& Introduction Over the past decades, savannah woodland management in the Sudanian region of Africa has focused on rotation and enrichment. To best manage these resources, it is critical to first understand the ecological processes influencing the behaviour of plants in their habitats. Previous work on the spatial patterns of trees has failed to account for the effects of plot size. & Methods Here, we determined the optimal plot size required to analyse and accurately represent the spatial patterns of trees. Five plot sizes (0.25–1.5 ha) from a representative stand of 2.25 ha were compared on the basis of simulations. We estimated the lengths of clumped radii and the strengths of the relationships between Isoberlinia spp. and subsidiary species using Ripley’s K(r) function. & Results The lengths of clumped radii (1.5–6 m) differed significantly with and were proportional to plot size. The spatial relationships between Isoberlinia spp. and subsidiary species were random, irrespective of plot size, but with a tendency towards repulsion. The spatial patterns of 1.0- and 1.5-ha plots were statistically similar to those of the main stand. & Conclusion Given the investigation costs, a plot size of 1.0 ha may be reasonably considered as suitable for behavioural studies of tree species in Sudanian ecosystems.
Keywords: Sudanian open woodland . Spatial pattern . Plot; size . Ripley’s K function . Isoberlinia . Benin . Savannah; woodland . Ecological niche